Bone Mineral Density in Gravida: Effect of Pregnancies and Breast-Feeding in Women of Differing Ages and Parity. (20th November 2014) - Lebel, Ehud; Mishukov, Yuri; Babchenko, Liana; Samueloff, Arnon; Zimran, Ari; Elstein, Deborah
Abstract : Changes of bone during pregnancy and during lactation evaluated by bone mineral density (BMD) may have implications for risk of osteoporosis and fractures. We studied BMD in women of differing ages, parity, and lactation histories immediately postpartum for BMD, T -scores, andZ -scores. Institutional Review Board approval was received. All women while still in hospital postpartum were asked to participate. BMD was performed by dual-energy X-ray absorptiometry (DXA) machine at femoral neck (FN) and lumbar spine (LS) by a single technician. Of 132 participants, 73 (55.3%) were ≤30 years; 27 (20.5%) were primiparous; 36 (27.3%) were grand multiparous; 35 (26.5%) never breast fed. Mean FNT -scores andZ -scores were higher than respective mean LS scores, but all means were within the normal limits. Mean LST -scores andZ -scores were highest in the grand multiparas. There were only 2 (1.5%) outliers with lowZ -scores. We conclude that, in a large cohort of Israeli women with BMD parameters assessed by DXA within two days postpartum, meanT -scores andZ -scores at both the LS and FN were within normal limits regardless of age (20–46 years), parity (1–13 viable births), and history of either no or prolonged months of lactation (up to 11.25 years).